Medicare's prescription drug program : competition issues and cost trends - Pattinson, Gloria R. (Health care in transition series., 2014)
The Medicare Prescription Drug, Improvement, and Modernization Act of 2003 (generally referred to as the Medicare Modernization Act, or MMA) substantially expanded the federal Medicare program by creating the prescription drug benefit known as Part D. In fiscal year 2013, Medicare Part D covered 39 million people. The federal government spent 59 billion net of premiums on Part D in that year; after accounting for certain payments from states under the program, the net federal cost was 50 billion, which represented 10 percent of net federal spending for Medicare. This book discusses the cost tr.